THE INFLUENCE OF EMOTIONS IN THE CHEMISTRY LEARNING PROCESS: A PHENOMENOLOGICAL STUDY OF ANXIETY AND LEARNING MOTIVATION - Damayanti, Yosephine Debbie; Wulanningtyas, Melania Eva (Universitas Negeri Semarang, 2025)
This study aims to understand the influence of emotions, especially anxiety and motivation, on the chemistry learning process. This study uses a qualitative approach with a phenomenological method, involving seven students from various levels of education. Students of the class of 2024 experience academic anxiety related to their choice of major, inability to attend lectures, and uncertainty about the future. Meanwhile, final year students face anxiety about completing their studies and the challenges of entering the workforce. The results of the study show that excessive anxiety has an impact on low student engagement in learning, especially in class discussions and problem solving. Students with high anxiety tend to rely on passive learning methods and have difficulty understanding chemistry concepts in depth. In contrast, high motivation plays a role in increasing academic engagement, building better conceptual understanding, and encouraging students to be more active in finding solutions to learning difficulties. These findings emphasize the importance of learning strategies that can reduce academic anxiety and increase student motivation. A more interactive learning approach and emotional support from the academic environment have the potential to create a more effective and productive learning experience. Thus, this study provides insights for educational institutions to design more adaptive strategies in improving the quality of chemistry learning.